Conversion of leucine to β‐hydroxy‐β‐methylbutyrate by α‐keto isocaproate dioxygenase is required for a potent stimulation of protein synthesis in L6 rat myotubes. Issue 1 (14th May 2015) - Girón, María D.; Vílchez, José D.; Salto, Rafael; Manzano, Manuel; Sevillano, Natalia; Campos, Nefertiti; Argilés, Josep M.; Rueda, Ricardo; López‐Pedrosa, José M.
Abstract: Background: L‐Leu and its metabolite β‐hydroxy‐β‐methylbutyrate (HMB) stimulate muscle protein synthesis enhancing the phosphorylation of proteins that regulate anabolic signalling pathways. Alterations in these pathways are observed in many catabolic diseases, and HMB and L‐Leu have proven their anabolic effects in in vivo and in vitro models. The aim of this study was to compare the anabolic effects of L‐Leu and HMB in myotubes grown in the absence of any catabolic stimuli. Methods: Studies were conducted in vitro using rat L6 myotubes under normal growth conditions (non‐involving L‐Leu‐deprived conditions). Protein synthesis and mechanistic target of rapamycin signalling pathway were determined. Results: Only HMB was able to increase protein synthesis through a mechanism that involves the phosphorylation of the mechanistic target of rapamycin as well as its downstream elements, pS6 kinase, 4E binding protein‐1, and eIF4E. HMB was significantly more effective than L‐Leu in promoting these effects through an activation of protein kinase B/Akt. Because the conversion of L‐Leu to HMB is limited in muscle, L6 cells were transfected with a plasmid that codes for α‐keto isocaproate dioxygenase, the key enzyme involved in the catabolic conversion of α‐keto isocaproate into HMB. In these transfected cells, L‐Leu was able to promote protein synthesis and mechanistic target of rapamycin regulated pathway activation equally to HMB. Additionally, these effects of leucine were reverted to a normal state by mesotrione, a specific inhibitor of α‐keto isocaproate dioxygenase. Conclusion: Our results suggest that HMB is an active L‐Leu metabolite able to maximize protein synthesis in skeletal muscle under conditions, in which no amino acid deprivation occurred. It may be proposed that supplementation with HMB may be very useful to stimulate protein synthesis in wasting conditions associated with chronic diseases, such as cancer or chronic heart failure.